Role Green Consumers in Mediating Relationship Between Environmental Awareness, Green Product Innovation, and Green Creativity on Competitive Advantage of SMEs - Gilang Kharisma Putra; Kuwatno Kuwatno; Jati Handarukmi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose this research is to test the concept of a green scope that has the potential to be adopted in achieving competitive advantage for SMEs. This is an explanatory study that tests the relationships between variables using a quantitative approach. In this study, the relationships among these variables will be explained through the relationship between Environmental Awareness, Green Process Innovation, and Green Product Innovation on the Competitive Advantage of SMEs through mediation by Green Consumer. The population in this study consisted of all MSME actors in Kendal Regency, totaling 16,508 units. Primary data was used, obtained directly by the researcher through distributing questionnaires in a hybrid manner. This study revealed that environmental awareness and green process innovation have a positive and significant effect on both competitive advantage and green consumer variables. Meanwhile, green product innovation has not been proven to affect either competitive advantage or green consumer. In mediation testing, the green consumer variable was proven to mediate the relationship between environmental awareness and green process innovation on competitive advantage, but the results were different for the relationship between green product innovation and competitive advantage. Research results encourage SMEs to have an understanding of and concern for the environment